AN ANALYSIS TYPES OF SLANG WORD FOUND IN GREEN DAY SONG LYRIC ALBUM - I Made Ardiana; I Made Iwan Indrawan Jendra; I Komang Sulatra (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
This study is entitled “An Analysis Types of Slang Word Found in Green Day Song Lyric Album”. The aim of this study is to identify the types of slang words that are found in the song lyrics of Green Day in the five albums: “1,039 Smoothed Out Slappy Hours” (1990), “Kerplunk !”(1991), “Dookie” (1994), “Father Of All..” (2020), and the last album “American Idiot” (2004). The method being used in this study is descriptive qualitative method and the technique is observation technique. The theory used was found in Kipfer and Chapman (2007). The study concludes that the secondary slang words are the only type that were found in the Green Day song lyrics